2007
DOI: 10.1093/jac/dkm304
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of conditions involved in the susceptibility of the dermatophyte Trichophyton rubrum to photodynamic treatment

Abstract: The results show that an optimal pH and low concentrations of calcium are crucial for a selective binding of Sylsens B to the fungus, leading to an increased PDT efficacy. This selective binding to T. rubrum cannot be accomplished for DP mme. It can be concluded that the prerequisite for successful treatment is a use of a low molarity solution of pH 5, supplemented with a chelating agent and a keratinase activity-repressing agent. Under these conditions, PDT with Sylsens B inactivates, initially via singlet ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 35 publications
1
41
0
8
Order By: Relevance
“…Pc 4-PDT also demonstrated an excellent safety profile in a phase 1 trial on cutaneous neoplasms (25). Although the susceptibility of T. rubrum to PDT using other photosensitizers has been extensively investigated in vitro, the mechanism of phototoxicity has not been clearly defined (2,9,(26)(27)(28). In this study, we showed that a common dose of Pc 4-PDT can induce cell death in microconidia (terbinafine-sensitive and -resistant strains of T. rubrum).…”
mentioning
confidence: 77%
“…Pc 4-PDT also demonstrated an excellent safety profile in a phase 1 trial on cutaneous neoplasms (25). Although the susceptibility of T. rubrum to PDT using other photosensitizers has been extensively investigated in vitro, the mechanism of phototoxicity has not been clearly defined (2,9,(26)(27)(28). In this study, we showed that a common dose of Pc 4-PDT can induce cell death in microconidia (terbinafine-sensitive and -resistant strains of T. rubrum).…”
mentioning
confidence: 77%
“…Photosensitizers, such as methylene blue and toluidine blue, have been shown to be a vital adjunct when using visible light to treat bacterial and fungal infections [19][20][21][22]. They are chosen on the basis of their charge, ability to be non-toxic without illumination (dark toxicity) and the ability to become genotoxic or mutagenic following irradiation [23].…”
Section: Biophotonicsmentioning
confidence: 99%
“…141,142 Other nonhematoporphyrin-derived photosensitizers (Sylsens B being the most effective) have also been shown to be efficacious in the treatment of onychomycosis. 143,144 Major concerns regarding effective drug penetration through thick, hyperkeratotic ungual barriers have led to introduction of new delivery methods involving iontophoretic and ultrasound devices, which enable increased nail bed permeability. 145,146 Most recently, one patient with treatment-resistant onychomycosis was successfully pretreated with a micro motor pneumatic diamond drill device and subsequent ALA-PDT with red light.…”
Section: Pdt In Microbial Diseases Virusesmentioning
confidence: 99%